Traffic light awareness routing - Muhammad Syahir Jailani (2016)
In this Final Year Project (FYP), we will be experimenting on the different ways in which we could reduce travelling time on the road in Singapore. The main focus of this project is to take into consideration the traffic lights on the road when planning a route for a particular destination. The project will simulate the outcomes of the different methods of routing. The result would then be analyzed to determine the best method of routing between two different points. The FYP will be focusing into three methods of routing. They are: (1) Traffic Light Awareness Routing (Fixed Probability), (2) Maximum travelling speed of road and (3) Traffic Light Awareness Routing (Quadratic Integer Problem). The main software that will be used in the project is the Simulation of Urban Mobility (SUMO) software. It is an open source software that is able to simulate different traffic conditions. The traffic map data used will be the traffic and road data of Singapore. It will be obtained by from OpenStreetMaps.com. The Graphical User Interface (GUI) that is used to simplify selection of choice for navigation is written in Java. From the data obtained in the research, it is hoped that a better and more robust routing system could be developed.